2006
DOI: 10.1007/s00221-006-0684-3
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in adaptation during childhood: the influences of muscular power production and segmental energy flow caused by muscles

Abstract: Acquisition of skillfulness is not only characterized by a task-appropriate application of muscular forces but also by the ability to adapt performance to changing task demands. Previous research suggests that there is a different developmental schedule for adaptation at the kinematic compared to the neuro-muscular level. The purpose of this study was to determine how age-related differences in neuro-muscular organization affect the mechanical construction of pedaling at different levels of the task.By quantif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Van Praagh and Doré speculated that the ability to coordinate synergistic and antagonistic muscle groups in a timely fashion could contribute to age-related differences in maximum power production . This speculation is supported the finding by Korff and Jensen that children demonstrated weaker intermuscular synergies in terms of segmental energy transfer between the synergistic muscle groups of the lower limb during submaximal cycling (Korff and Jensen, 2007).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Van Praagh and Doré speculated that the ability to coordinate synergistic and antagonistic muscle groups in a timely fashion could contribute to age-related differences in maximum power production . This speculation is supported the finding by Korff and Jensen that children demonstrated weaker intermuscular synergies in terms of segmental energy transfer between the synergistic muscle groups of the lower limb during submaximal cycling (Korff and Jensen, 2007).…”
Section: Discussionsupporting
confidence: 84%
“…Therefore, one might have expected that age-related differences in overall maximum power production could be due to the children's lack of ability to produce power at the individual joints of the lower limbs. This speculation is substantiated by findings from Korff and Jensen, who showed that during submaximal cycling children's relative maximum power at the hip joint was less than that of adults (Korff and Jensen, 2007). Our findings contradict this speculation as during our maximum cycling task children produced greater relative peak joint powers at both the knee and the hip joint.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations